Light and freshwater discharge drive the biogeochemistry and microbial ecology in a sub-Arctic fjord over the Polar night - Vonnahme, T. R.; Klausen, L.; Bank, R. M.; Michellod, D.; Lavik, G.; Dietrich, U.; Gradinger, R. (Frontiers in Marine Science, 2022)
The polar night has recently received increased attention as a surprisingly active biological season. Yet, polar night microbial ecology is a vastly understudied field. To identify the physical and biogeochemical parameters driving microbial activity over the dark season, we studied a sub-Arctic fjord system in northern Norway from autumn to early spring with detailed monthly sampling. We focused on the impact that mixing, terrestrial organic matter input and light have on the dynamics of the microbial ecosystem. Our study highlights strong seasonal differences in the key drivers during spring, autumn, and winter. The spring bloom starts while the water column is still fully mixed, opposing the traditional critical depth hypothesis. We identified incident solar radiation as the key driver for a spring bloom starting in March. However, it takes until April before the bloom reaches substantial chlorophyll biomass. The autumn bloom is controlled by vertical mixing, driving nutrient upwelling and dilution of zooplankton grazers, which had their highest biomass during this time. We suggest that the dilution-recoupling hypothesis stating that dilution of zooplankton by vertical mixing is crucial to reduce grazing stress and allow a bloom formation is crucial for the autumn bloom. We found that even a short period with a lack of terrestrial runoff due to subzero temperatures in combination with strong winds was able to mix the water column, triggering an October/November autumn bloom. During the light-limited polar night primary production was extremely low, but bacteria continued growing on decaying algae and their exudates, but also allochthonous organic matter. We suggest that a melting event in January could fuel a mid-winter bacteria bloom. In conclusion, polar night biogeochemistry and microbial ecology is not only driven by light availability, but strongly affected by freshwater discharge and land-ocean coupling. With climate change freshwater discharge is increasing in the Arctic, which will likely increase importance of the dynamics described in this study.